Actualization of Pancasila Philosophy in the Context of Family Social Resilience in Jalawastu Traditional Village, Brebes Regency, Central Java, Indonesia - Ardi, Mohammad Noviani; Santoso, Heri; Nizar, Muchamad Coirun; Tulab, Tali (El-Usrah: Jurnal Hukum Keluarga, 2024)
The development of the modernization era significantly influences changes in social behavior among individuals. Families, as the smallest social structures within society, are not immune to these changes and must adapt by understanding the values associated with family social resilience. This article aims to analyze family social resilience within the Jalawastu traditional village, located in Brebes Regency, Central Java Province, through the lens of Pancasila philosophical values. The study employs a qualitative methodology utilizing a grounded theory model to examine family life in the Jalawastu traditional village. Primary data were collected through interviews with customary administrators, traditional leaders, and members of the local community. Additionally, several scholarly articles and other studies served as secondary data sources. In analyzing the value of Pancasila philosophy in relation to the collected data, this study draws upon Soekarno's writings and other pertinent literature. The findings indicate that the social resilience of families in the Jalawastu traditional village is commendable. Each family member prioritizes familial values by respecting one another, maintaining communication, and fulfilling the respective functions and responsibilities of each member. Furthermore, they consistently uphold spiritual values within the family to mitigate conflict. In addition, they foster a sense of brotherhood among other families, which contributes to the robust social resilience of their own family unit. This framework demonstrates that families in the Jalawastu traditional village profoundly embody the cultural and religious values of the Pancasila philosophy. Consequently, this condition may serve as an ideal model for family social resilience in contemporary society.